“It Feels Like My Spine is About to Break”: Experience and support needs of family caregivers of children with cerebral palsy in Ethiopia - Melkitu Melak; Solomon Mekonnen; Afolasade Fakolade; Beata Batorowicz (PLoS ONE, 2026)
Background Due to the complex and long-term care needs of children with Cerebral Palsy (CP), caregivers often face an overwhelming caregiving burden, and they experience physical and psychological strain. Few studies in Sub-Saharan Africa have indicated that caregivers face financial difficulties and limited access to formal support services. However, evidence is scarce in Ethiopia. Objectives This study aimed to explore the caregiving experiences and support needs of family caregivers of children with CP in Ethiopia. Method An exploratory descriptive qualitative design was used in this study. A purposeful sampling method was employed to identify and select 13 family caregivers of children with CP. Face-to-face, semi-structured, in-depth individual interview was used to collect data. The interview was conducted in the local language, Amharic. The audio data were transcribed verbatim manually and imported to NVivo version 14 software for analysis. Reflexive thematic analysis was used to analyze the data. Results Four themes were identified: the emotional journey of caregivers, daily caregiving demands, impact of caregiving, and support systems and support needs. Caregiving for children with CP negatively affected the emotional, physical and social well-being of caregivers. Caregivers indicated a need for financial support, psychological support, adequate healthcare service, access to assistive devices, and education for their children with CP. Conclusion The findings emphasize the urgent need for interventions that address the financial vulnerabilities of caregivers, provide targeted psychosocial support, and enhance access to healthcare, assistive devices and education for children with CP.